Pemberdayaan Anggota Kelompok Pengajian Aisiyah Kebraon Surabaya Melalui Pengembangan Produk Berbasis Ecoprint - Awal Putra Suprianto; Utari Anggita Shanti; Fera Ratyaningrum; Siti Mutmainah; Agung Ari Subagio (PT. Penerbit Riset Sadwa, 2026)
This community service program was implemented to empower members of the Aisiyah Kebraon Surabaya Study Group through the development of creative skills based on ecoprint techniques. The main problems faced by partners include limited access to structured training, minimal production facilities, and low self-confidence in participants in utilizing their creative potential. To overcome these problems, the activity was implemented through a participatory training method with a hands-on approach and ongoing technical mentoring. The activity stages included introduction, application, and evaluation of results, with a focus on the application of environmentally friendly natural dyeing techniques. The results of the activity showed a significant increase in the understanding of basic ecoprint concepts, the ability to use materials and tools, and the skills to produce products with aesthetic value and economic potential. In addition, this training also fostered a collaborative spirit and environmental awareness among participants. This program demonstrates that a practice-based training approach and systematic mentoring are effective in increasing the creative capacity of women at the community level and supporting sustainable development based on local wisdom. Keyword: Ecoprint, Textile craft, Women empowerment, Ecological, Natural materials